A new parameter in COVID-19 pandemic: initial lactate dehydrogenase (LDH)/Lymphocyte ratio for diagnosis and mortality - Istemi Serin; Nagehan Didem Sari; Mehmet Hilmi Dogu; Sakine Damla Acikel; Gulnıhal Babur; Avni Ulusoy; Mediha Irem Onar; Emre Cem Gokce; Oguz Altunok; Feyza Yaylaci Mert; Ayse Karakilic; Muhammed Baltik; et al. (Elsevier, 2020)
Background: COVID-19 (Coronavirus Disease-2019) is a pandemic disease, infecting more than 26.5 million people. Since there is no specific and effective treatment; early diagnosis and optimal isolation of the patient are of vital importance. Real-time polymerase chain reaction-based (RT-PCR) analyses do not achieve sufficient sensitivity in the diagnosis of the disease. Methods: The data from 2217 patients diagnosed as COVID-19 between March 2020 and June 2020 and hospitalized or discharged with home isolation were retrospectively analyzed. Demographic data, comorbidities, PCR results, initial computed tomography (CT), laboratory values, Lactate Dehydrogenase (LDH)/Lymphocyte ratio, initial treatments and last status were recorded. The diagnostic sensitivity of LDH/Lymphocyte ratio, which is the main purpose of the study, was analyzed statistically. Results: In order to test the effectiveness of LDH/Lymphocyte ratio for COVID-19 for diagnostic purposes, CT results were considered as gold standard. The area under the curve (AUC) was found to be 0.706 (p < 0.001; cut-off > 0.06) (Sensitivity: 76.4, specificity: 59.60). For the evaluation of LDH/Lymphocyte ratio in terms of survival, AUC was found to be 0.749 (p < 0.001; cut-off > 0.21) (Sensitivity: 70.59, specificity: 73.88). Conclusion: Studies based on radiological findings have demonstrated that CT involvement has higher sensitivity. LDH/Lymphocyte ratio was analyzed in terms of diagnosis and mortality with using specific CT involvement as gold standard method which was found to be a more sensitive due to PCR false negativity; 0.06 and 0.21 were obtained as cut off values for diagnosis and mortality.